2007
DOI: 10.1111/j.1538-7836.2007.02657.x
|View full text |Cite
|
Sign up to set email alerts
|

Fondaparinux combined with intermittent pneumatic compression vs. intermittent pneumatic compression alone for prevention of venous thromboembolism after abdominal surgery: a randomized, double‐blind comparison

Abstract: Summary. Background: The benefit of combined mechanical and pharmacologic methods for venous thromboembolism prevention after abdominal surgery has not been clearly established. Objectives: To compare the efficacy and safety of fondaparinux in conjunction with intermittent pneumatic compression vs. intermittent pneumatic compression alone in this context. Patients and Methods: This was a randomized, double-blind, placebo-controlled superiority trial. Patients aged at least 40 years undergoing abdominal surgery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
81
1
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(86 citation statements)
references
References 33 publications
2
81
1
2
Order By: Relevance
“…13 Two of other abdominal surgery. 19 In this study, the risk of any VTE (including asymptomatic DVT) was 69% lower in the fondaparinux group, and fondaparinux was associated with a possible reduction in the risk of proximal DVT (RR, 0.14; 95% CI, 0.02-1.14), but there was only one case of symptomatic VTE in each of the treatment groups. Major bleeding was more common among those who received fondaparinux (RR, 10.2; 95% CI, 1.31-79.7), but differences between the groups in fatal bleeding and bleeding requiring reoperation were neither confi rmed nor excluded.…”
Section: Lmwh Vs No Prophylaxismentioning
confidence: 53%
“…13 Two of other abdominal surgery. 19 In this study, the risk of any VTE (including asymptomatic DVT) was 69% lower in the fondaparinux group, and fondaparinux was associated with a possible reduction in the risk of proximal DVT (RR, 0.14; 95% CI, 0.02-1.14), but there was only one case of symptomatic VTE in each of the treatment groups. Major bleeding was more common among those who received fondaparinux (RR, 10.2; 95% CI, 1.31-79.7), but differences between the groups in fatal bleeding and bleeding requiring reoperation were neither confi rmed nor excluded.…”
Section: Lmwh Vs No Prophylaxismentioning
confidence: 53%
“…14 In 4 trials the comparator was enoxaparin (40 mg once daily in 2 trials and 30 mg twice daily in 2 trials), 10 -13 in 1 trial the comparator was dalteparin 5000 IU once daily, 15 and in 3 trials the comparator was placebo. 14,16,17 …”
Section: Trial Detailsmentioning
confidence: 99%
“…10 -17 Two trials involved patients undergoing hip fracture surgery, 11,14 2 hip replacement surgery, 12,13 1 major knee surgery, 10 2 elective abdominal surgery, 15,17 and 1 acutely ill high-risk medical patients. 16 …”
Section: Study Eligibilitymentioning
confidence: 99%
“…Several clinical trials have demonstrated not only its antithrombotic efficacy but also its favorable safety profile, including its prevention of VTE in patients undergoing major orthopedic surgery or high-risk abdominal surgery [3,4]. In the randomized, double-blinded APOLLO study, the combination of intermittent pneumatic compression (IPC) and FPX reduced the incidence of VTE after abdominal surgery by 69.8% relative to IPC alone, with a low bleeding risk compared to placebo [5]. However, there are few studies evaluating the safety and efficacy of FPX after CRC surgery.…”
Section: Introductionmentioning
confidence: 99%